Buddhist Architecture in East Asia - Yu, Shuishan; Yan, Aibin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This issue focuses on the Buddhist architecture in East Asia. Over the last 2000 years, Buddhism had transformed not only the intellectual and practical lives but also the built environments of East Asia. The articles in this issue aim to capture the scope and diversity of East Asian Buddhist architecture and delineate the front lines of research in the field. In this collection, without bypassing the significant topics of famous temples, influential monasteries, and monumental landmarks, we try to restore a more balanced picture of Buddhist practice and the built environment by incorporating buildings and planning from the overlooked regions and aspects of Buddhism. Studies here feature shrines and temples in small villages as well as those in sacred mountains, forms reshaped by contemporary life as well as those of historical events, and practices in the domestic realm as well as those with pilgrimage significance. We want to go beyond the well-established scholarships on stylistic changes, technical development, and the typological studies of halls and pagodas in China, Japan, and Korea. There are in-depth discussions of examples from regions and cultures of religious hybridity, analyzing the way architecture is built for and shaped by the practices of a given community, integrated into the spiritual and material lives, and share themes and concepts to foster a comprehensive culture that sustains life and identity of a place. These are significant issues not only for the scholarship on architectural history, but also meaningful for the contemporary building of our own life and faith.